FEATURES OF THE SEED DORMANCY IN UMBELLIFER CROPS CAUSED BY VARIOUS FACTORS - D. N. Baleev; A. F. Bukharov; M. I. Ivanova (Овощи России, 2017)
Experiments were carried out at FGBNU VNIIO in 20112016. The aim of the study was to analyze the influence of different types of organic dormancy caused by various factors on seed quality of some representatives of umbellifer crops. The objects of the study were seeds: parsnip ‘Kulinar’ (Pastinaca sativa L.); carrot ‘Rogneda’ (Daucus carrota L.); root parsley ‘Ljubasha’ (Petroselinum crispum (Mill.) Nyman ex A.W. Hill.); root celery ‘Kupidon’ (Apium graveolens L.); coriander ‘Yantar’ (Coriandrum sativum L.) and dill ‘Kentavr’ (Anethum graveolens L.). In all seeds studied, the speed of embryo growth was decreased by 30% or0.03 mma day. Under influence of the induced dormancy caused by incubation in extract from dill seeds, the speed of embryo growth in all species was decreased by 94-97% on average. The process of germination of just picked seeds in all crops studied showed itself in reduction of germinated seed number by 54% as compared with control variant. Under the effect of incubation at high temperature the seeds of parsnip and root celery didn’t germinate, whereas the germination in the seeds of coriander, root parsley and carrot was decreased by 51%, 47% and 46%, respectively as compared with control. There is no germination observed in parsnip, carrot, root celery and coriander under influence of induced dormancy caused by incubation in extract from dill seeds. In this case, the germination of seeds of root parsley and dill was 8.1% and 15%, respectively. The Pearson correlation between the speed of embryo growth and percent of seed germination showed the significant and positive relationship in the range 0.706-0.952. Analysis of variance (ANOVA) showed that induced by temperature or allelopathic dormancy had impact on the speed of embryo’s growth in the crops studied, where factor effect was 89-86% depending on type of dormancy. Analysis of variance between the factors of dormancy and germination revealed that all types of dormancy analyzed had much influence on germination in these crops. The factor effects for primary, temperature induced, and induced allelopathic dormancy were 98% (F=1590.3; P=< 2x10-16), respectively.